(untitled) (Palimpsesto, 2021)
What you can feel, what you can sense and communicate from Luis Arturo Ramos’s (1947) poetics, are semiotic aspects understudied by the critics. Even when every essay or note of “This Was a Cat” define its every argument, story or plot, the conjectural aspect of its structure is overlooked. These pretenses have given me the excuse to venture within two main topics: the speech’s aesthetic aspect and the conjectural character imposed by the reiterative phrase from start to finish, “Do you want me to tell you the story again?”, and which serves as the leitmotiv of the classic endless tale.